A requirements engineering methodology based on natural language syntax and semantics - Andreou, Andreas S.; Pattichis, Constantinos S.; Georgiades, Marinos G. (My University, 2005)
The present paper proposes a methodology for engineering requirements in a precise, comprehensive, understandable and time-saving way based on concepts and principles of Natural Language Syntax and Semantics (NLSS). The NLSS methodology copes with the following phases: (i) requirements discovery, by emphasizing on the creation and application of specific questions sets; (ii) requirements analysis, by stressing issues such as classification, decomposition and terminology of requirements; and (Hi) requirements specification, by focusing on the writing formalization of the requirements. © 2005 IEEE.
Keywords: Language processing; Specifications; Requirements engineering